2021
DOI: 10.3389/fpsyt.2021.626859
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Chinese Version of the 10-Item Ruminative Response Scale Among Undergraduates and Depressive Patients

Abstract: Objective: Rumination is considered as a key process in the mechanism of depression. Assessing rumination is important for both research and clinical practice. The Ruminative Response Scale (RRS) is a widely-used instrument to measure rumination. This study aimed to examine the psychometric properties of the Chinese 10-item Ruminative Response Scale (RRS-10) in a large sample of Chinese undergraduates and depressive patients.Methods: A total of 1,773 university students and 286 clinical patients with major dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…While the S-AI examines state anxiety depending on specific circumstances, the T-AI measures trait anxiety and anxious tendencies regardless of situation. For the S-AI and T-AI, scores ≤ 52 and ≤54 are seen to reflect normal anxious tendencies, respectively [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…While the S-AI examines state anxiety depending on specific circumstances, the T-AI measures trait anxiety and anxious tendencies regardless of situation. For the S-AI and T-AI, scores ≤ 52 and ≤54 are seen to reflect normal anxious tendencies, respectively [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Responses are summed to create a total score with higher values indicating more frequent brooding. Existing research provides strong support for the reliability and factorial validity of RRS‐B scores across diverse clinical, community, and undergraduate samples (He et al, 2021; Schoofs et al, 2010; Thanoi & Klainin‐Yobas, 2015; Treynor et al, 2003). Internal consistency for this sample was excellent ( α = 0.84).…”
Section: Methodsmentioning
confidence: 99%
“…It had been employed in a study involving cognitive measures of the impact of nature viewing [75]. Studies have demonstrated the ability of the scale to capture within-person variation in depressive brooding [76] and real changes in rumination over a two-month period [77]. The present study employed the translated and validated 13-item symptom-based rumination subscale, with high concurrent validity with Beck Depression Inventory (r = 0.79, p < 0.001) in the Taiwanese population [78].…”
Section: Measurementsmentioning
confidence: 99%